تجليات ثورة 1919 في الشعر المصري: The manifestations of the 1919 revolution in Egyptian poetry - أ د . وائل علي السيد (JAR, 2023)
The Egyptian revolution took place on the ninth of March 1919 AD against the British occupier, and all sects of the Egyptian people and all national forces participated in it, and even poets in particular. Therefore, this research deals with its impact on Egyptian poetry, which was said at a crucial stage in the history of the homeland, and it became a record of its events, and it was one of the weapons taken by the fighters for freedom and dignity. Among the poets whose poetry the revolution manifested itself and sang about, among them are: Ahmad Muharram, Ahmad Naseem, Hassan al-Qayati, Ahmad al-Kashef, Muhammad Abd al-Muttalib, Ahmad Abu al-Najat. In the face of this huge amount of poems that were said on the occasion of the revolution, and the follow-up of its events, we can say with confidence that the poetry of this stage chronicled the revolution with an accurate history. The research includes the following topics: the development of national poetry and national anthems after the revolution, experiencing the events of the revolution and interacting with its facts, satire and denouncing the occupation, supporting the leaders of the revolution, calling for unity and rejecting division, the role of women in the revolution, the image of the nation’s leader in the eyes of poets.